Natural history of nonalcoholic fatty liver disease: A prospective follow‐up study with serial biopsies. Issue 2 (27th December 2017) - Nasr, Patrik; Ignatova, Simone; Kechagias, Stergios; Ekstedt, Mattias
Abstract : Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease in the world. The complete natural history of NAFLD is unknown because few high‐quality follow‐up studies have been conducted. Our aim was to find variables predicting disease severity through an extended follow‐up with serial biopsies. In a prospective cohort study, 129 patients who enrolled between 1988 and 1993 were asked to participate in a follow‐up study on two occasions; biochemical, clinical, and histologic data were documented. The mean time between biopsies was 13.7 (±1.7) and 9.3 (±1.0) years, respectively. At the end of the study period, 12 patients (9.3%) had developed end‐stage liver disease and 34% had advanced fibrosis. Out of the 113 patients with baseline low fibrosis (<3), 16% developed advanced fibrosis. Fibrosis progression did not differ among the different stages of baseline fibrosis ( P  = 0.374). Fifty‐six patients (43%) had isolated steatosis, of whom 9% developed advanced fibrosis (3 patients with biopsy‐proven fibrosis stage F3‐F4 and 2 patients with end‐stage liver disease). Fibrosis stage, ballooning, and diabetes were more common in patients who developed end‐stage liver disease; however, there were no baseline clinical, histologic, or biochemical variables that predicted clinical significant disease progression. Conclusion : NAFLD is a highly heterogeneous disease, and it is surprisingly hard to predict fibrosis progression. Given enough time, NAFLD seems to have a more dismal prognosis then previously reported, with 16% of patients with fibrosis stage <3 developing advanced fibrosis and 9.3% showing signs of end‐stage liver disease. ( Hepatology Communications 2018;2:199–210)